The Efficacy of Using Round Robin Technique in Teaching Speaking to Indonesian English as Foreign Language (EFL) Students - Yanpitherszon Liunokas (Institut Agama Islam Negeri Palopo, 2022)
This research aims at finding out the efficacy of using round robin technique in teaching speaking especially to Indonesian English as Foreign Language (EFL) students. The main question of this research: Is the use of round robin technique effective in teaching speaking to Indonesian EFL students? The research can be an addition to the persisting teaching speaking in English. The research was conducted in August 2022. This research was conducted at First semester students of the English Study Program of Nusa Cendana University, Kupang. The population of this research was First semester students of the English Study Program of Nusa Cendana University, Kupang in the 2021/2022 academic year. The number population is 160 in four classes. The research used a pre-experimental method with a pre-test and post-test design. The pre-test was given to find out the basic ability of the students in mastering speaking and the post-test given to find out the students’ improvement in mastering speaking after giving the treatment by using round robin technique. The findings show that using round robin technique is effective in teaching speaking to Indonesian EFL students. It is supported by the result of the significance test through SPSS 20 program that the P was 0.00. Therefore, it is recommended to use the round robin technique in developing students’ speaking of Indonesian EFL students